Module MA1132 (Frolov), Advanced Calculus Tutorial Sheet 11 To be solved during the tutorial session Thursday/Friday, 7/8 April 2015 Name: 1. Compute the integral Z In (A, B) = ∞ −∞ Z ∞ exp − ··· −∞ n X xi Aij xj + 2 i,j=1 n X ! Bi xi dx1 · · · dxn , i=1 where A = (Aij ) is a positive-definite symmetric n × n matrix. Solution: Let us introduce the column x with entries xi and the column B with entries Bi . Then we can write in matrix form n n X X − xi Aij xj + 2 Bi xi = −xt · A · x + 2B t · x , (1) i,j=1 i=1 where · denotes the matrix multiplication, and t denotes matrix transposition. Then using that At = A we can write (complete the square) −xt · A · x + 2B t · x = −(x − A−1 · B)t · A · (x − A−1 · B) + B t · A−1 · B = −y t · A · y + B t · A−1 · B , where y = x − A−1 · B. Thus, the integral In (A, B) is equal to Z ∞ Z ∞ t t −1 In (A, B) = ··· e−y ·A·y+B ·A ·B dy1 · · · dyn −∞ Z−∞∞ Z ∞ t B t ·A−1 ·B =e ··· e−y ·A·y dy1 · · · dyn . −∞ (2) (3) −∞ Since A is symmetric it can be diagonalised by an orthogonal matrix A = O · Λ · Ot , Λ = diag(λ1 , . . . , λn ) , λi > 0 ∀i , O : O · Ot = I . (4) Now, we make the following change of variables y =O·z ⇔ yi = n X Oij zj . (5) j=1 The Jacobian matrix is (∂yi /∂zj ) = Oij . Since O is orthogonal one gets J = det(∂yi /∂zj ) = ±1 . Thus the integral takes the form Z ∞ Z ∞ t t B t ·A−1 ·B In (A, B) = e ··· e−y ·O·Λ·O ·y dy1 · · · dyn Z−∞ Z−∞ ∞ ∞ t −1 t = eB ·A ·B ··· e−z ·Λ·z dz1 · · · dzn Z−∞ Z−∞ ∞ ∞ Pn t −1 2 = eB ·A ·B ··· e− i=1 λi zi dz1 · · · dzn −∞ −∞ Z ∞ n t −1 B t ·A−1 ·B e eB ·A ·B n/2 −z 2 =√ e dz =√ π . λ1 · · · λn λ1 · · · λn −∞ 1 (6) Since λ1 · · · λn = det A, we finally get In (A, B) = eB π n/2 √ . det A t ·A−1 ·B (7) 2. Find the volume Vn,h of an n-simplex ∆n x1 ≥ 0 , . . . , x n ≥ 0 , ∆n : x1 + x2 + · · · + xn ≤ h . (8) Solution: From the definition of ∆n we get 0 ≤ xn ≤ h − x1 − x2 − · · · − xn−1 . (9) Thus, the projection of ∆n onto the hyperplane xn = 0 is the n − 1-simplex ∆n−1 , and Z h−x1 −···−xn−1 Z Z Z Z dx1 · · · dxn = · · · dxn dx1 · · · dxn−1 . (10) Vn,h = · · · ∆n−1 ∆n Repeating the procedure we get Z Z h Z h−x1 Vn,h = ··· 0 0 0 h−x1 −···−xn−1 dxn · · · dx2 dx1 . (11) 0 Making the change x1 = hξ1 , x2 = hξ2 , . . . , xn = hξn , (12) one gets n Vn,h = h αn , Z 1 1−ξ1 Z αn ≡ Vn,1 = Z ··· 0 0 1−ξ1 −···−ξn−1 dξn · · · dξ2 dξ1 . (13) 0 On the other hand comparing αn with (11), one sees that αn is equal to Z 1−ξ1 −···−ξn−1 Z 1 Z 1−ξ1 Z 1 αn = ··· dξn · · · dξ2 dξ1 = (Vn−1,1−ξ1 ) dξ1 0 0 0 0 Z 1 αn−1 . = αn−1 (1 − ξ1 )n−1 dξ1 = n 0 (14) Taking into account that α1 = 1, one finds αn = 1 , n! (15) Vn,h = hn . n! (16) and finally 2